Copper gallium selenide thin films on Si by magnetron sputtering for photovoltaic applications: Composition, junction formation and metal contacts. Issue 1 (1st January 2018) - Awaah, M. A.; Obahiagbon, U.; Mohammed, H.; Akpa, O.; Awaah, I.; Isaac-Smith, T.; Korivi, N.; Posthill, J. B.; Das, K.
Abstract: Thin films of CuGaSe were deposited on n -Si (1 0 0) by rf magnetron sputtering from a stoichiometric CuGaSe2 target. The objective of this study was to characterize the thin film/Si heterojunction for potential photovoltaic applications, evaluate possible candidates for metal contacts and to establish whether heteroepitaxial growth could be achieved, particularly as the mismatch of lattice parameters corresponding to the base of the copper gallium selenide (CGS) tetragonal cell is quite close to that of Si, with a 2.9% mismatch. For this study, Si substrates were prepared by the standard Radio Corporation of America (RCA) cleaning procedure immediately followed by the deposition of CGS by sputtering at a substrate temperature of 600°C. The deposited thin-film stoichiometry and morphology were characterized by Rutherford backscattering spectroscopy (RBS) and transmission electron microscopy (TEM). Rutherford back scattering (RBS) analysis indicated a thin-film composition of Cu1 Ga1 Se1 indicating that the films were Se deficient, although channeling was not observed. The polycrystalline nature of the deposited thin film was established by cross-sectional TEM. An estimated 1.5-nm thick layer likely to be SiO x was observed at the CGS–Si interface. It is believed that this interfacial layer prevented heteroepitaxy CGS on Si. Additionally, circular metal contacts were deposited on the thin films and characterized by capacitance and current–voltage measurements. It was observed that Al and Ag contacts were rectifying, from which the thin-film carrier density was estimated to be ~5 × 10 15 and ~7.68 × 10 15  cm −3 with Al and Ag contacts, respectively. Au, Pt, W and Cr were ohmic, and Mo and Ni provided semi-ohmic contacts to CGS films.